Placebo-controlled study of transcranial magnetic stimulation treatment influence on motor symptoms in patients with Parkinson's disease stage II - Demchenko, A. V.; Aravitskaya, Dj. N.; Revenko, A. V.; Aravitskiy, E. O.; Демченко, Аліна Вікторівна; Аравіцька, Джаміля Нуреддінівна; Ревенько, Алла Василівна; Аравіцький, Євген Олегович (My University, 2021)
Aim of the study: to investigate influence of TMS treatment on motor symptoms of PD patients stage II using parameters of SPES SCOPA Motor Scale and motor evoked potential (MEP) latency.
Keywords: тези доповідей